PENGARUH KONSENTRASI BIOURINE SAPI PADA SISTEM HIDROPONIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI PAKCOY (Brassica Rapa L.) - Saputra, I Made Arya; Sujana, Putu; Suryana, I Made (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2020)
Chemical pakcoy cultivation on agricultural land has a negative impact on the health of the human body, one of the solutions to overcome this is to use cow biourine organic material in the hydroponic system. Furthermore, a study was held entitled "The effect of Concentration of Cow BioUrine on the Hydroponic System on the Growth and Yield of Mustard Pakcoy (Brassica Rapa L.)". This study aims to determine the effect of giving bio-concentration of cow urine on the hydroponic system on the growth and yield of Pakcoy mustard plants. until January 2, 2020. This study used a Randomized Block Design (RBD) consisting of 6 treatments namely K1: cow Biournine concentration of 100 ml / 1 liter K2 raw water: cow Biournine concentration 200 ml / 1 liter K3 raw water: cow Biournine concentration 300 ml / 1 liter K4 raw water: cow Biournine concentration 400 ml / 1 liter K5 raw water: cow Biournine concentration 500 ml / 1 liter K6 raw water: cow biournine concentration 600 ml / 1 liter raw water and repeated 4 times so that 24 treatments were obtained. The results of this study indicate that the administration of cow urine bio concentration has a significant effect on all parameters except the parameters of the oven dry weight of the plant root and the highest growth and yield of plants is obtained at the administration of 500 ml of cow urine / 1 liter of raw water (K5). total fresh plant is 63.51 g and total oven dry weight is 3.17 g.